2021
DOI: 10.3390/cancers13236003
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Targeted Agents Used to Treat Paediatric ALK-Positive ALCL

Abstract: Non-Hodgkin lymphoma (NHL) is the third most common malignancy diagnosed in children. The vast majority of paediatric NHL are either Burkitt lymphoma (BL), diffuse large B-cell lymphoma (DLBCL), anaplastic large cell lymphoma (ALCL), or lymphoblastic lymphoma (LL). Multi-agent chemotherapy is used to treat all of these types of NHL, and survival is over 90% but the chemotherapy regimens are intensive, and outcomes are generally poor if relapse occurs. Therefore, targeted therapies are of interest as potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 182 publications
0
2
0
Order By: Relevance
“…Among targeted therapies, brentuximab vedotin (BV), a CD30-directed antibody conjugated to the antitubulin agent monomethyl auristatin E (MMAE), represents a new therapeutic option, having shown a 53% overall response and manageable side effects when investigated as single agent in paediatric relapsed/refractory patients. 8,9 The prognostic role of minimal disseminated disease (MDD) in ALCL, measured by quantitative reverse transcription PCR (qRT-PCR), in peripheral blood (PB) has been extensively demonstrated. 10,11 In addition, the Associazione Italiana di Ematologia e Oncologia Pediatrica (AIEOP) and Berlin-Frankfurt-Münster (BFM) groups demonstrated that the early evaluation of minimal residual disease (MRD) in NPM::ALK-positive ALCL identifies patients with a very high relapse risk and inferior survival.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…Among targeted therapies, brentuximab vedotin (BV), a CD30-directed antibody conjugated to the antitubulin agent monomethyl auristatin E (MMAE), represents a new therapeutic option, having shown a 53% overall response and manageable side effects when investigated as single agent in paediatric relapsed/refractory patients. 8,9 The prognostic role of minimal disseminated disease (MDD) in ALCL, measured by quantitative reverse transcription PCR (qRT-PCR), in peripheral blood (PB) has been extensively demonstrated. 10,11 In addition, the Associazione Italiana di Ematologia e Oncologia Pediatrica (AIEOP) and Berlin-Frankfurt-Münster (BFM) groups demonstrated that the early evaluation of minimal residual disease (MRD) in NPM::ALK-positive ALCL identifies patients with a very high relapse risk and inferior survival.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…8 Nevertheless, as for ALK-rearranged lung carcinomas, mechanisms of resistance may develop, including acquired ALK mutations. 18 Mutational profiling of ALK + ALCL has revealed NOTCH1 mutations in 20% of the cases. NOTCH1 expression is also induced via STAT3 activation mediated by the ALK fusion protein.…”
Section: Anaplastic Large Cell Lymphomas Alk-positivementioning
confidence: 99%
“…Although rare, there have been several documented cases of ALK-positive pcALCL (pcALCL) diagnosed on skin biopsy without evidence of secondary systemic involvement. This paradox poses several challenges in the classification, prognostication, treatment, and follow-up of these patients (4,(7)(8)(9). Here we present a review of current literature regarding adult and pediatric ALK-positive ALCL without evidence of systemic involvement on initial diagnosis.…”
Section: Introductionmentioning
confidence: 97%